2018
DOI: 10.1016/j.tube.2018.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Application of multiplexed ion mobility spectrometry towards the identification of host protein signatures of treatment effect in pulmonary tuberculosis

Abstract: Rationale:The monitoring of TB treatments in clinical practice and clinical trials relies on traditional sputum-based culture status indicators at specific time points. Accurate, predictive, blood-based protein markers would provide a simpler and more informative view of patient health and response to treatment.Objective:We utilized sensitive, high throughput multiplexed ion mobility-mass spectrometry (IM-MS) to characterize the serum proteome of TB patients at the start of and at 8 weeks of rifamycin-based tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 61 publications
(71 reference statements)
1
20
0
Order By: Relevance
“…SAA1 has been reported to be upregulated in lung parenchyma and bronchi of patients with COPD compared with smoking controls (Lopez-Campos et al, 2013). During TB treatment, SAA1 expression is reduced, and the reduction is greater for patients who culture-converted at later time points (Sigal et al, 2017;Kedia et al, 2018). In our study, this gene was found to be downregulated in OM cholesteatoma and COPD large airway brushings, but upregulated in CRS.…”
Section: Discussionsupporting
confidence: 50%
“…SAA1 has been reported to be upregulated in lung parenchyma and bronchi of patients with COPD compared with smoking controls (Lopez-Campos et al, 2013). During TB treatment, SAA1 expression is reduced, and the reduction is greater for patients who culture-converted at later time points (Sigal et al, 2017;Kedia et al, 2018). In our study, this gene was found to be downregulated in OM cholesteatoma and COPD large airway brushings, but upregulated in CRS.…”
Section: Discussionsupporting
confidence: 50%
“…bovis-infected cattle. In human TB, the SAA level was significantly higher in TB patients than in healthy controls, and it was also significantly increased in TB patients with lung lesions and tended to decline in patients undergoing TB treatment (2931). The AGP level was found to be increased in active TB patients and may be a possible marker of a slow response to anti-TB treatment (32).…”
Section: Discussionmentioning
confidence: 99%
“…If these observations can be extended, emphasis should be placed on replacing the invasive BALF procedure with a more easily obtained sample. Analysis of serum samples by multiplexed ion mobility spectrometry similarly shows a similar decrease of acute phase proteins in response to antibiotic treatment and culture status (Kedia et al, 2018 ). This supports the clinical translatability of identified BALF markers being applied for blood-based testing.…”
Section: Discussionmentioning
confidence: 90%